PENGARUH MODEL PEMBELAJARAN BIOLOGI BERBASIS KONSTRUKTIVIS-KOLABORATIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS X SMA NEGERI 2 KARANGANYAR TAHUN PELAJARAN 2012/2013 - Utami, Nova Indri; Prayitno, Baskoro Adi; Santosa, Slamet (Universitas Sebelas Maret, 2015)
The aim of this research is to ascertain the influence of collaborative- constructivist learning models toward critical thinking ability of X grade students at SMA Negeri 2 Karanganyar in academic year 2012/2013. This research was quasi experiment research which used posttest only nonequivalent control group design. The population of this research was all of X grade students at SMA Negeri 2 Karanganyar in academic year 2012/2013. Sampling techniques used cluster sampling that choosed X6 as experiment group and X7 as control group. Data was collected using test and non test. Test method using critical thinking test. Non test method using observation sheet and document. The hypotheses analyzed by t-test. This research concluded that application of collaborative- constructivist learning models has real influential toward critical thinking ability of X grade students at SMA Negeri 2 Karanganyar. Keywords: Collaborative-Constructivist Learning Model, Critical Thinking Ability